INTRODUCING CHILDREN’S LITERATURE BY MAXIMAZING TABTALE'S INTERACTIVE BOOKS AT DIGITAL DEVICES - Titik Wahyuningsih (Universitas Negeri Padang, 2013)
The rapid development of technology has changed children’s attention mostly to computer and its all-things rather than to paper based things. This way, story books for children may become untouched things that lead to the unheard of strange things to children. If the condition happens, language acquisition, cultural understanding, and moral teaching and all the advantages of tales reading will then come into only a fantasy. TabTale’s interactive storybooks provide an exciting and rich reading experience on iPad, iPhone and other digital devices. With over 25 million downloads TabTale's interactive books, games and educational apps provide a new interactive experience full of innovative activities which inspire children’s creativity and imagination as well as help caring parents to educate their lovable children in a uniquely enjoyable and fun way. As brilliant interactive books for kids, TabTale provide many famous stories for children in which in each title not only can we enjoy the story but games as well. Thus, children can help the characters inside the stories to do certain things, tap a character and see how it transforms, opt whether to read the story by themselves and record the sound or let the media read for them so they know the best way to pronounce the words, do puzzles in between the readings, paint the pictures, count objects, match pictures, and else. Thus, the variations of activities inside motivate children to know more and understand any aspects of education they should get in their early stage of life.